Molecular mechanisms involved in the anticancer activity of BISPMB in oesophageal cancer cells - Siyo, Vuyolwethu Penelope (Division of Medical Biochemistry, 2016)
BisPMB (E, Z)-1,8-(Bis-p-methoxyphenyl)-2,3,7-trithiaocta-4-ene 7-oxide) is a synthetic analogue of the garlic compound ajoene. It is 12 times more active at inhibiting the growth of oesophageal squamous cell carcinoma WHCO1 cells and displays selectivity for cancer cells over normal cells. BisPMB is therefore attractive as a potential cancer therapeutic. In this study, bisPMB was found to inhibit WHCO1 cancer cell proliferation in a time and concentration dependent manner with 24 hour IC50's between 6.7 - 8.1 μM against a range of oesophageal cancer cell lines including WHCO1, KYSE30 and WHCO6. The normal oesophageal epithelial cell line, HET1A was found to be five times less responsive to bisPMB. Furthermore, bisPMB was found to induce apoptosis and G2/M cell cycle arrest in WHCO1 cells. Gene expression data obtained from the microarray analysis showed that bisPMB primarily targets the unfolded protein response (UPR) in WHCO1 cells. We also found that bisPMB deregulated the ER stress genes involved in protein processing in the endoplasmic reticulum and also deregulated MAPK pathways in WHCO1 cells. At a protein level, bisPMB was found to induce an increase in protein ubiquitination and in the expression of ER stress and UPR genes ATF4, Grp78 and CHOP in WHCO1 cells. We also observed a decrease in ATF6 90 kDa protein and transient XBP-1 mRNA splicing. The activation of p38, JNK and ERK MAPK pathways in bisPMB treated WHCO1 cells was also observed. Furthermore siRNA mediated knock-down of CHOP abolished the anti-proliferative effect of bisPMB in WHCO1 cells. However, inhibition of JNK and p38 MAPK by chemical inhibitors, SP600125 and SB 203580 respectively, had no effect on bisPMB antiproliferative activity against WHCO1 cells. On the other hand, inhibition of ERK1/2 MAPK by U0126 enhanced the anti-proliferative effect of bisPMB in WHCO1 cells. These results support the hypothesis that ER stress and MAPK signalling pathways are essential for bisPMB induced cytotoxicity in oesophageal cancer cells.